2010
DOI: 10.1007/s12192-010-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential stress responses among newly received calves: variations in reductant capacity and Hsp gene expression

Abstract: Bovine respiratory disease complex (BRD), a major economic concern to the beef cattle industry all over the world, is triggered by physical, biological and psychological stresses. It is becoming noticeable that the key to reducing BRD appears to be centered at reducing the response to stress. The aims of the present study were to detect individual variations in the stress response of newly received young calves through their leukocyte heat shock protein (Hsp) response, selected neutrophil-related gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Several authors have reported individual variability in physiological stress responses in cattle (e.g. Loerch and Fluharty, 1999;Eitam et al, 2010) and lambs (Rice et al, 2016b) when introduced to a feedlot. Lambs with a high cortisol response during the 1 st week in this new environment were also more reactive during isolation and restraint tests and had a greater number of feeding bouts likely due to a high number of displacements.…”
Section: Exploring the Feeding Environmentmentioning
confidence: 99%
“…Several authors have reported individual variability in physiological stress responses in cattle (e.g. Loerch and Fluharty, 1999;Eitam et al, 2010) and lambs (Rice et al, 2016b) when introduced to a feedlot. Lambs with a high cortisol response during the 1 st week in this new environment were also more reactive during isolation and restraint tests and had a greater number of feeding bouts likely due to a high number of displacements.…”
Section: Exploring the Feeding Environmentmentioning
confidence: 99%
“…Moreover, Glenske et al (2011) reported a low relationship between the dopamine receptor D4 (DRD4) gene located near QTL for behavioural traits on chromosome 29, and temperament of German Angus cattle. A study using the expression of the leucocyte heat shock protein (Hsp) gene for early detection of the subclinical signs of bovine respiratory disease complex (BRD) confirmed that this gene is associated with stress response of animals (Eitam et al, 2010).…”
Section: Candidate Genes For Behavioural Traits In Cattlementioning
confidence: 99%
“…It includes upper and lower respiratory tract infections, diphtheria and pneumonia [ 1 , 2 ]. Due to immature functionality of the respiratory system in young cattle [ 3 ], BRD occurs more frequently and severely at young age, regardless of immunological and management considerations [ 4 , 5 ]. BRD is the most costly feedlot disease due to prevention and treatment costs, morbidity, mortality, and production amortization that includes performance, carcass merit, meat tenderness and palatability [ 1 , 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, methods for detecting morbid cattle involve subjective visual appraisal and depend on the stage and extent of the disease. However, clinical signs of BRD may often go undetected in feedlot calves [ 15 ], emphasizing the need of an objective and reliable early risk predictor [ 5 ]. Genomic-based approaches may thus serve as additional methods for control of BRD.…”
Section: Introductionmentioning
confidence: 99%